Aortainsufficiens hos häst : patofysiologi och behandling - Bergenwall, Sebastian (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2010)
Aortic insufficiency is a very common valve problem in horses and most often affects older individuals, but nevertheless existent within younger ones. The root cause for aortic insufficiency can be varied, for example; endocarditis, ventricular septum defect or congenital valve disease but the most common are progressive valve degeneration or elite competition. Depending on the root cause, different changes can be observed on the aorta valves, but they do all have the same effect, the valves do not seal properly and blood leaks backwards.